Array of Bose-Einstein condensates under time-periodic Feshbach-resonance management - Abdullaev, F. Kh [UNESP]; Tsoy, E. N.; Malomed, B. A.; Kraenkel, Roberto André [UNESP] (American Physical Society (APS), 2003)
The investigation of the dynamics of a discrete soliton in an array of Bose-Einstein condensates under the action of a periodically time-modulated atomic scattering length [Feshbach-resonance management (FRM)] was discussed. The slow and rapid modulations, in comparison with the tunneling frequency were considered. An averaged equation, which was a generalized discrete nonlinear Schrödinger equation, including higher-order effective nonlinearities and intersite nonlinear interactions was derived in the case of the rapid modulation. It was demonstrated that the modulations of sufficient strength results in splitting of the soliton by direct simulations.
Keywords: Approximation theory; Atomic physics; Chaos theory; Gas condensates; Mathematical models; Nonlinear equations; Oscillations; Solitons; Nonlinear interactions; Nonlinear lattices; Gas dynamics